2023
DOI: 10.2460/javma.22.10.0445
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi infection diagnosed in dogs in nonendemic areas and results from a survey suggest a need for increased Chagas disease awareness in North America

Abstract: OBJECTIVE To describe the clinical presentation and outcome in dogs diagnosed with Trypanosoma cruzi infection in nonendemic areas and to survey veterinary cardiologists in North America for Chagas disease awareness. ANIMALS 12 client-owned dogs; 83 respondents from a veterinary cardiology listserv. PROCEDURES A retrospective, multicenter medical records review to identify dogs diagnosed with American trypanosomiasis between December 2010 and December 2020. An anonymous online survey was conducted August 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…A similar level of infection was reported among shelter dogs in Louisiana [33]. Much like the situation with human Chagas disease, there is increasing recognition of the translocation of infected dogs, often from the southern to northern U.S., where the veterinary community may have minimal awareness of Chagas disease [34].…”
Section: T Cruzi Infection In Non-humans Is a Crucial Problem And An ...mentioning
confidence: 55%
“…A similar level of infection was reported among shelter dogs in Louisiana [33]. Much like the situation with human Chagas disease, there is increasing recognition of the translocation of infected dogs, often from the southern to northern U.S., where the veterinary community may have minimal awareness of Chagas disease [34].…”
Section: T Cruzi Infection In Non-humans Is a Crucial Problem And An ...mentioning
confidence: 55%
“…5,17,18 Investigation into the role of benznidazole treatment for T cruzi infection in naturally infected dogs has been limited partly because of the lack of availability of the medication, knowledge of which animals will benefit from treatment, and lack of veterinary awareness of Chagas disease. 4,17 Consequently, the role of benznidazole treatment for T cruzi infection in dogs has not been well established, and treatment options remain limited.…”
Section: Discussionmentioning
confidence: 99%
“…Although the observed trypanocidal effects and limitation of cardiac damage, ECG, and echocardiographic abnormalities are encouraging, none of the studies has reported clinical outcomes related to progression of heart failure, mortality rates, survival time, or quality of life in affected dogs 5,17,18 . Investigation into the role of benznidazole treatment for T cruzi infection in naturally infected dogs has been limited partly because of the lack of availability of the medication, knowledge of which animals will benefit from treatment, and lack of veterinary awareness of Chagas disease 4,17 . Consequently, the role of benznidazole treatment for T cruzi infection in dogs has not been well established, and treatment options remain limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation